(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
This research work aims at estimating the potential level of gross alpha and beta concentrations in sediments geographical region of Southern, Delta State, Nigeria via gas-filled proportional counter (Protean Instrument Corporation MPC 2000DP). Thirty sediment samples were collected from the river bed and analyzed and the mean obtained results ranged from BDL to 27.56±2.62 Bq/kg and 173.5±229 Bq/kg to 3853.0 Bq/kg with average value of 9.689±3.95 Bq/kg and 1479.7±256.6 Bq/kg respectively. It was practically clear that gross beta activities values generally exceeded alpha activities values in all the samples which implies that beta emitter may be the dominant radionuclide in the area. When the obtained results were compared with the control values (3.212±0.64 Bq/kg for alpha and 82.9±13.26 Bq/kg for beta), it was observed that the obtained results exceeded that of control results, since there is no standard for gross alpha and beta activities. The obtained high values of gross alpha and beta activities could possibly be attributed to area geological formation, hydrocarbon waste effluent discharge into the environment and waste released from marine operations. However, sediment may be use for construction provided appropriate modern scientific solidification/stabilization (S/S) treatment will be done to the hydrocarbon and marine waste before being discharged into the environment. It is a matter of concern to residents of the studied communities to use sediment for construction. Hence government agency responsible for enforcing environment and radiological policies should do so to ensure compliance by all shareholders.